Three-Component Coupling Reactions Involving Arynes, Phosphites, and Aldehydes toward 3-Mono-Substituted Benzoxaphosphole 1-Oxides - Kim, Han Byeol; Jeong, Hee Jin; Cheong Jaeeun; Lee, Jae Kyun; Lee, Duck-Hyung; Han, Seojung (American Chemical Society, 2023)
A mild,efficient, and transition-metal-free three-component couplingreaction involving arynes, phosphites, and aldehydes was establishedto afford 3-mono-substituted benzoxaphosphole 1-oxides. A range of3-mono-substituted benzoxaphosphole 1-oxides was obtained from botharyl- and aliphatic-substituted aldehydes in moderate to good yields.Moreover, the synthetic utility of the reaction was demonstrated bya Gram-scale reaction and the transformation of the products intovarious P-containing bicycles.